Liver Support System and Transplant-Free Survival Patients with Liver Failure: An Evidence-Based Case Report - Aravinda Pravita; Kresna Adhiatma; Juferdy Kurniawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: The mortality rate in patients with acute liver failure (ALF) and acute on chronic liver failure (ACLF) is still very high. Currently, liver support systems are an alternative therapy in bridging liver transplantation. However, its effectiveness in reducing mortality is still controversial when compared to standard medical therapy (SMT). Our study aims to review the efficacy of liver support system compared to standard medical therapy (SMT) among acute liver failure patients without liver transplantation.Method: We conducted systematic literature searching using PubMed/MEDLINE, EBSCO-CINAHL, ProQuest, and Cochrane databases. Selected articles were examined for duplicates and were screened by abstract and title. Then, we appraised the articles based on the critical appraisal tools from Centre for Evidence-Based Medicine (CEBM) University of OxfordResults: One systematic review and meta-analysis of randomized control trials study was extracted after thorough research. Alhamshi et al showed that extracorporeal liver support has significantly reduced mortality in both ALF and ACLF patients as the primary outcome. Other main findings about adverse events including hepatic encephalopathy, thrombocytopenia, bleeding, and infection were still unclear.Conclusion: The use of liver support system demonstrated better outcome in reducing mortality to standard medical therapy in transplant free patients with liver failure, but best modality recommendation was inconclusive.